Kedisiplinan Wajib Zakat-Pajak Masyarakat Di Daerah Aek Loba (Studi Kasus Masyarakat Aek Loba, Kabupaten - Sri Nurul Hasanah (Al-Sharf: Jurnal Ekonomi Islam, 2022)
Taxes and zakat are one of the incomes for the state for the benefit of the people. The purpose of this study was to determine the strategy for optimizing the income of zakat-tax funds in increasing community discipline in the Aek Loba area. This research method uses a descriptive method with a qualitative approach. Informants will choose information by going directly to the field for data collection obtained based on facts and data in the field. Data sources are primary and secondary data sources through data collection techniques: (1) Observation, (2) Interview, and (3) Documentation. To test the validity of the data, it is necessary to have: (1) strength, (2) triangulation and, (3) reference. For data analysis techniques include: (1) data reduction, (2) data presentation and, (3) conclusions or levers. The final result of this research is there is a need for more socialization of zakat-tax obligations and also improve services in field practice.